EFFECT OF SORBITOL AND BORON SPRAYING ON VEGETATIVE GROWTH AND FLOWERING OF STRAWBERRY FRAGARIA ANANASSA DUCH. CV. RUBY GEM - Moulin, Humaid Rashid; Obaid, Iyad Assi (Journal of agricultural, environmental and veterinary sciences, 2019)
A field experiment was conducted at one of greenhouse belonged to College of agriculture – Diyala University. IRAQ, at fall season 2017 – 2018 in order to study the effect of foliar spray three concentrations of Sorbitol(0, 25, 50 gL-1) and Boric acid (B17%) at concentrations(0, 20, 40 mgL-1) on some growth vegetative and flowering of strawberry plant (Fragaria ananassa Duch) cv. Rubygum. using (R.CB.B.D) design with four replicate The result showed, the Sorbitol ,Boron and their interaction had significant effect on studied characters, The application of sorbitol at at 25 gL-1 spraying caused a significant increase in leave number, leaf area, plant leave area ,the vegetative dry weight. 57.880 leaf plant-1, 37.122 cm2.plant-1, 0.21482 m2.plant-1, 278.50 g.plant-1, respectively compared with control, also spraying of boric acid at 40mgL-1 recorded a significant increase in leave number, leaf area, plant leave area, the root dry weight reached 57.58 leaf plant-1, 36.975 cm2.plant-1, 0,21518 m2.plant-1, 11.669 g.plant-1 respectively, Whereas control treatment gave the lowest means of the above characters. The interaction between Sorbitol at 25gL-1 and Boron at 40mgL-1 spraying caused a significant increase in leave number, leaf area, plant leave area ,the, the vegetative dry weight, the root dry weight, reached to 65.890 leave.plant-1, 39.772 cm2.leave, 0.26228m2.plant-1, 84.670g.plant-1, 15.39 g.plant-1, respectively compared with control which gave the lowest means of the above characters. as well as spraying of the interaction between sorbitol at 0 and Boron at 20 mgL-1 gave a significantly increasing in number of flower reached 104.155 flower.plant-1 ,while the control recorded a lowest number of flower (82.274 flower.plant-1).
Keywords: Strawberry; Sorbitol; boron